2018
DOI: 10.1111/jgs.15642
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment that Does Not Progress to Dementia: A Population‐Based Study

Abstract: Background/Objective In population studies, most individuals with mild cognitive impairment (MCI) do not progress to dementia in the near term, but rather remain stable MCI or revert to normal cognition. Here, we characterized MCI subgroups with different outcomes over 5 years. Setting/Participants A population‐based cohort (N=1603). Measurements Clinical Dementia Rating (CDR); self‐reported medical conditions, subjective cognitive concerns, self‐rated health, depressive symptoms, blood pressure, medications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 47 publications
5
83
0
1
Order By: Relevance
“…The MCI to NC reversion rate has been reported to range from 10-50%, although it varies depending on the follow-up period and MCI subtype [3,4]. In a previous study with the study population similar to ours and follow-up, the reversion rate was 35% [22], which is similar to the rate of 33.3% in our study [22].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The MCI to NC reversion rate has been reported to range from 10-50%, although it varies depending on the follow-up period and MCI subtype [3,4]. In a previous study with the study population similar to ours and follow-up, the reversion rate was 35% [22], which is similar to the rate of 33.3% in our study [22].…”
Section: Discussionsupporting
confidence: 84%
“…Longitudinal studies have shown that mild cognitive impairment (MCI), which has clinical significance as a precursor of dementia, reverts to normal cognition (NC) function [3,4]. In previous studies investigating factors related to reversion from MCI to NC function, modifiable factors, such as memory, visual spatial cognitive function, neuropsychological function, personality, and lifestyle, have been reported [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…33 African Americans are less likely than whites to enroll in clinical trials that use biomarkers to improve diagnostic accuracy of aMCI. 35 Our study suggests that by demonstrating memory deficits on more than one memory test or test occasion, false-positive diagnoses of aMCI may be avoided. 35 Our study suggests that by demonstrating memory deficits on more than one memory test or test occasion, false-positive diagnoses of aMCI may be avoided.…”
Section: Discussionmentioning
confidence: 73%
“…34 Therefore, community studies are still needed to validate diagnostic criteria in this underrepresented population. 35 Our study suggests that by demonstrating memory deficits on more than one memory test or test occasion, false-positive diagnoses of aMCI may be avoided. This is particularly important to ensure that all persons who are assessed for MCI, particularly those in minority groups who may be vulnerable to false-positive and false-negative diagnoses, receive appropriate treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, in previous MCI longitudinal studies, many MCI cases did not develop dementia but reverted to normal cognition (NC) [12,13]. Cognitive function, demographics, genetic data, personality, and lifestyle activities have been reported as factors associated with recovery from MCI to NC [13][14][15][16][17]. A meta-analysis reveals that factors such as young age, high educational level, and Mini-Mental State Examination (MMSE) score are more likely to revert from MCI to NC without APOEe4 allele, hypertension, and stroke.…”
Section: Introductionmentioning
confidence: 99%